Increased levels of reduced cytochrome b and mitophagy components are required to trigger nonspecific autophagy following induced mitochondrial dysfunction - Deffieu, Maika (The Company of Biologists, 2013)
Mitochondria are essential organelles producing most of the energy required for the cell. A selective autophagic process called mitophagy removes damaged mitochondria, which is critical for proper cellular homeostasis; dysfunctional mitochondria can generate excess reactive oxygen species that can further damage the organelle as well as other cellular components. Although proper cell physiology requires the maintenance of a healthy pool of mitochondria, little is known about the mechanism underlying the recognition and selection of damaged organelles. In this study, we investigated the cellular fate of mitochondria damaged by the action of respiratory inhibitors (antimycin A, myxothiazol, KCN) that act on mitochondrial respiratory complexes III and IV, but have different effects with regard to the production of reactive oxygen species and increased levels of reduced cytochromes. Antimycin A and potassium cyanide effectively induced nonspecific autophagy, but not mitophagy, in a wild-type strain of Saccharomyces cerevisiae; however, low or no autophagic activity was measured in strains deficient for genes that encode proteins involved in mitophagy, including ATG32, ATG11 and BCK1. These results provide evidence for a major role of specific mitophagy factors in the control of a general autophagic cellular response induced by mitochondrial alteration. Moreover, increased levels of reduced cytochrome b, one of the components of the respiratory chain, could be the first signal of this induction pathway.